Does Kinesiophobia Effect One Day Physical Activity Behaviour and Functionality of Young People with Ankylosing Spondylitis? - DEMİRBÜKEN, İLKŞAN; POLAT, MİNE GÜLDEN (MARMARA UNIV, INST HEALTH SCIENCES, 2020)
Objective: The aim of this study was to investigate the relationship between kinesiophobia, physical activity behaviour and functionality in patients with ankylosing spondylitis (AS). Methods: This study included 57 participants (mean age, 30.8 +/- 5.19 years) in 2 groups of AS and healthy controls. One day physical activity behaviour was evaluated with tri-axial accelerometer. Tri-axial accelerometer was recorded physical activity domains and intensities for 24 hours. Participants completed clinical questionnaires assessing pain, kinesophobia, disease activity, and functionality. Kinesiophobia and pain were quantified by the Tampa Scale for Kinesiophobia and Short-Form McGill Pain Questionnaire. Function and disease activity were rated by using the Bath Ankylosing Spondylitis Functional Index, and Bath Ankylosing Spondylitis Disease Activity Score. Results: There was no correlation between kinesiophobia and one day physical activity behaviour in AS patients group. There was a negative correlation between high physical activity level and disease activity(p<0.05, r:-.519) and there was a negative correlation between high and moderate physical activity levels, and functionality (p <0.05, r:-.555 r-395, respectively). Conclusion: According to the results of this study showed that; there was a relationship between disease activity, functionality, and one day physical activity behaviour. On the other hand, there was not any relation between pain intensity, kinesophobia and data obtained from accelerometer. Further studies with larger sample size and longer time periods should be carried out to reveal physical activity behaviours and its related factors in AS patients who will survive with this disease for years.
Keywords: ankylosing spondylitis; disease activity; functionality; kinesophobia; physical activity; QUALITY-OF-LIFE; MCGILL PAIN QUESTIONNAIRE; TURKISH VERSION; DISEASE-ACTIVITY; RELIABILITY; DISABILITY; VALIDITY; INDEX; FEAR